DAMPAK PELAKSANAAN KURIKULUM MERDEKA BELAJAR TERHADAP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Siregar, Nuryanti; Hanani, Silfia; Sesmiarni, Zulfani; Ritonga, Pitriani; Pahutar, Elisah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to find out how the implementation of the independent curriculum at Al-Husnayain Panyabungan Mandailing Natal Integrated Islamic High School and find out the impact of the implementation of the independent curriculum and constraints on the implementation of the independent curriculum at Al-Husnayain Panyabungan Mandailing Natal Integrated Islamic High School. This research uses qualitative types. Primary data sources were obtained from teachers, principals, vice principals for curriculum, PAI teachers, administration and students in high school Integrated Islam Al-Husnayain Panyabungan Mandailing Natal. Data collection is done through observation, interviews and documents. Data validity is done by extension of participation, persistence of observation, and triangulation. Data analysis is carried out by data reduction, presentation and drawing conclusions. The results showed that (1) The implementation of the independent curriculum at Al-Husnayain Panyabungan Mandailing Natal Integrated Islamic High School went smoothly, well and actively. (2). The Impact of the Independent Curriculum on Learning of Integrated Islamic PAI Darul Hasan Al-Husnayain Panyabungan Mandailing Natal is: a. Positive impact, namely relevant and contextual learning, development of critical and analytical thinking activities, strengthening moral values and science, developing attitudes of tolerance and openness and increasing student involvement b. Negative impacts, namely curriculum fragmentation, understanding gaps, reduced focus on spiritual aspects and limited resources, resistance from stakeholders, integration of technology and the role of parents and society.